2023
DOI: 10.1111/raq.12825
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral activity of currently used medicinal plants in aquaculture and structure–activity relationship of their active ingredients

Abstract: Aquaculture is an important source of high‐quality protein and plays a crucial role in ensuring global food security. However, viral diseases have caused significant damage to aquaculture production, making it necessary to develop effective measures to treat them. Although drugs are commonly used to treat viral diseases, recent studies have shown that crude extracts of medicinal plants and their active ingredients have potential applications in the treatment of aquatic viral diseases. Furthermore, natural smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…Herbal extracts act as immunostimulants to boost fish immune responses against bacterial, fungal, viral, and parasitic diseases [ [11] , [26] ]. According to several research, medicinal herbs can improve fish's non-specific immune responses (innate immune responses) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herbal extracts act as immunostimulants to boost fish immune responses against bacterial, fungal, viral, and parasitic diseases [ [11] , [26] ]. According to several research, medicinal herbs can improve fish's non-specific immune responses (innate immune responses) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the antioxidant effects and regulation of the body's immunity and induction of sedation, it has also been effective in mood regulation 17 . Medicinal plants and natural products are useful sources of novel and safer compounds for drug withdrawal management 18 . Prosopis farcta has been used in the treatment of neurological disorders and pains 19 .…”
Section: Introductionmentioning
confidence: 99%
“…17 Medicinal plants and natural products are useful sources of novel and safer compounds for drug withdrawal management. 18 Prosopis farcta has been used in the treatment of neurological disorders and pains. 19 Some of the phytochemicals in this plant are toxin, quercetin, tryptamine, apigenin, 5-5-hydroxytryptamine,L-arabinose, and luteolin.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine, including crude plant extracts, natural compounds, and their analogs (8), act as important sources of therapeutic agents and have been frequently applied in the diseases treatment of humans, poultry, and livestock with high bioactivity and bioavailability as well as minimal side effects (9)(10)(11). For example, it was found that the natural compounds resveratrol, epigallocatechin gallate, and quercetin, which belonged to the polyphenols, exhibited significant antiviral activity against severe acute respiratory syndrome coronavirus, Zika virus, and dengue virus (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that the natural compounds resveratrol, epigallocatechin gallate, and quercetin, which belonged to the polyphenols, exhibited significant antiviral activity against severe acute respiratory syndrome coronavirus, Zika virus, and dengue virus (12)(13)(14)(15). In recent decades, phytomedicines have also been widely used in aquaculture and some natural compounds have been reported against aquatic animal viral diseases (8). For instance, for grass carp hemorrhagic disease, magnolol and honokiol extracted from Magnolia had a significant inhibitory effect on the replication of grass carp reovirus in vitro and in vivo via activating the host antiviral immune response (16,17).…”
Section: Introductionmentioning
confidence: 99%